2012
DOI: 10.1111/j.1440-1746.2011.06875.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin and misoprostol on bacterial translocation in portal hypertensive rats

Abstract: In this study, bacterial translocation occurred in portal hypertension. Melatonin and misoprostol reduced the incidence of bacterial translocation in portal hypertensive rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The cytoprotective effect following separate administration of misoprostol and melatonin reported by others, and verified by us, encouraged us to evaluate their combined local effect [50]. This resulted in a complete abolishment of the SDS-induced increase in CL Cr-EDTA .…”
Section: Discussionsupporting
confidence: 55%
“…The cytoprotective effect following separate administration of misoprostol and melatonin reported by others, and verified by us, encouraged us to evaluate their combined local effect [50]. This resulted in a complete abolishment of the SDS-induced increase in CL Cr-EDTA .…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, tuberculosis chemotherapy using isoniazid is improved by melatonin (Wiid et al , ). Melatonin administration also reduced the incidence of bacterial translocation in intestinal ischaemia/reperfusion (Sozen et al , ), major liver resection (Cetinkaya et al , ), and in rats with portal hypertension (Topuz et al , ). Intriguingly, melatonin therapy exerted anti‐inflammatory effects but did not reduce neuronal injury in a rabbit model of either Gram‐positive Streptococcus pneumoniae or Gram‐negative Escherichia coli meningitis; these failures may be attributed to the 12 h delay in the administration of melatonin after the infection (Spreer et al , ).…”
Section: Defensive Effects Of Melatonin Against Bacterial Pathogensmentioning
confidence: 99%
“…In summary, a reduced expression of AA‐NAT and ASMT results in lower melatonin levels. The reduced melatonin levels may favour the translocation of bacteria and increase the incidence of infection; these changes are inhibited by melatonin administration (Cetinkaya et al , ; Sozen et al , ; Topuz et al , ) (Figure ). In summary, melatonin may serve as a novel antibiotic to defend against bacterial pathogens, and the possible mechanisms involve the suppression of NF‐κB and STAT1 (Figure B).…”
Section: Defensive Effects Of Melatonin Against Bacterial Pathogensmentioning
confidence: 99%
“…Misoprostol, an FDA-approved synthetic prostaglandin E1 analog (PGE1), has mucosal cytoprotective and antisecretory effects and is also used off-label to induce labor. It has been shown that misoprostol inhibits bacterial translocation, modifies bacterial clearance in mice after a burn injury (61, 62), and has cytoprotectant properties against mucosal radiation (61, 62). Misoprostol has multiple uses with different combinations with lidocaine, metronidazole, pentoxifylline, and gentamicin as a wound healing agent for decubitus ulcers or diabetic foot lesions (63).…”
Section: Discussionmentioning
confidence: 99%